2009
DOI: 10.17221/1616-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some terricolous lichens [Cladonia rangiformis Hoffm., Peltigera neckerii Hepp ex Müll. Arg., Peltigera rufescens (Weiss) Humb.] on soil bacteria in natural conditions

Abstract: This paper is aimed to investigate the effects of some terricolous lichens on soil bacteria's growth in natural conditions. It is focused on species of bacteria and also on numbers of colony of soil specimens that were taken from substrates of three different terricolous lichen species. Peltigera rufescens (Weiss) Humb., which has not secondary metabolites, did not show an inhibition effect on soil bacteria. However, Peltigera neckerii Hepp ex Müll. Arg., which has secondary metabolites, has a negative effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…; Land & Lundström ; Halama & Van Haluwin ; Türk et al . ; Ranković, Mišić & Sukdolak ; Akpinar, Ozturk & Sinirtas ). The effect of reducing CBSC concentrations on the rates of both consumption and decomposition were correlated with initial concentrations of medullary but not cortical CBSCs.…”
Section: Discussionmentioning
confidence: 99%
“…; Land & Lundström ; Halama & Van Haluwin ; Türk et al . ; Ranković, Mišić & Sukdolak ; Akpinar, Ozturk & Sinirtas ). The effect of reducing CBSC concentrations on the rates of both consumption and decomposition were correlated with initial concentrations of medullary but not cortical CBSCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the antibacterial activity of extracts of Cladonia sp. has been revealed in the laboratory (Rankovic et al 2009) and in the field (Akpinar et al 2009). Squamarina lentigera , a species with similar chemical characteristics to Cladonia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the lichens mentioned above contain secondary compounds (Appendix S4), which are believed to have antimicrobial and allelopathic properties, among other functions (Lawrey 1989; Fahselt 1994; Gauslaa 2004), but the ecological roles of these substances are largely unknown, and could be multi‐faceted. Several studies have shown the negative influence of many lichen substances on bacteria and fungi in the laboratory and the field (Sedia & Ehrenfeld 2003; Tay et al 2004; Akpinar et al 2009). Recent studies have also found a strong reduction in both the available nitrate and potential nitrification rate beneath BSC‐forming lichens in different environments (including gypsum ecosystems close to our study area; Castillo‐Monroy et al 2010; Delgado‐Baquerizo et al 2010), suggesting that microbial communities may be inhibited under these organisms (Sedia & Ehrenfeld 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Türkiye'de farklı liken türlerine ait özütlerin antibakteriyel ve antifungal aktiviteleri üzerine yapılmış pek çok çalışma bulunmaktadır (29)(30)(31) Çalışmamızdan elde edilen veriler ile literatürde yer alan diğer çalışmaların sonucunda, P. saxatilis ve P. sulcata aseton özütlerinin E. coli üzerinde antibakteriyel etkinliklere sahip olduğu ve bu sonuçlar değerlendirildiğinde, bu türlerin gerekli testler gerçekleştirildikten sonra antibiyotiklere yardımcı ya da alternatif olabilecek potansiyel biyolojik materyaller arasında yer alabilecekleri ortaya koyulmuştur. Aynı liken türlerinin antibakteriyel etkinliklerinde görülen farklılıklar, örneklerin toplandığı bölgelere ve özüt çıkarır-ken kullanılan çözücülere göre değişebilmekte-dir.…”
Section: Discussionunclassified